A evoluç\~ao da abrangência do Programa Abono Salarial: Análise dos fluxos de entrada e saída (2011-2019) - Brunu Amorim; Sandro Pereira Silva (Instituto de Pesquisa Econômica Aplicada (IPEA), 2022)
– This study aimed to investigate the recent operational dynamics of the Abono Salarial Program in Brazil, with a time horizon between 2011-2019. The analysis took into account occurrences that may have affected the number of people eligible for the program, such as, for example, the strong retraction of the economy and, consequently, of the level of employment in 2015 and 2016. Therefore, the analytical focus fell on the inflows and outflows of workers, seeking to relativize them with the general flows of the formal labor market. The main data source was the Annual Report of Social Information (Rais), on which specific tabulations were performed to estimate the flows of eligible workers in each year. Some of the main conclusions: i) the movement of formal occupation was a fundamental factor for the growth in the number of eligible people between 2011 and 2019, with its greatest effect for those who were joining or leaving Rais; ii) the groups of workers that gained more access to the formal market had a relative increase in the total number of eligible workers; iii) the dynamics of the number of workers who became eligible among those who already had a formal job from one year to the next showed differences in terms of compliance with the criteria, with emphasis on the time criterion; and iv) the minimum wage policy has an influence on the number of people eligible for the Abono Salarial, mainly due to its influence on the remuneration criterion.
10419/284856
Keywords: 330; employment and income policies; Abono Salarial Program; labor market; social security